2003
DOI: 10.1144/gsl.sp.2003.206.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Models of Rodinia assembly and fragmentation

Abstract: Amongst existing palaeogeographic models of the Rodinia supercontinent, or portions thereof, arguments have focused upon geological relations or palaeomagnetic results, but rarely both. A new model of Rodinia is proposed, integrating the most recent palaeomagnetic data with current stratigraphic, geochronological and tectonic constraints from around the world. This new model differs from its predecessors in five major aspects: cratonic Australia is positioned in the recently proposed AUSMEX fit against Laurent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(154 citation statements)
references
References 141 publications
(112 reference statements)
4
143
1
2
Order By: Relevance
“…The pre-1.45 Ga paleomagnetic record is fragmentary, but is reasonable for the period 1.45-1.0 Ga (e.g., Elming et al, 2014;Pisarevsky et al, 2014). There is a >200 Ma gap in reliable Laurentian paleomagnetic data between ~1000 and ~790 Ma, followed by another ~100 Ma gap between ~720 and 615 Ma (e.g., Pisarevsky et al, 2008;Pisarevsky et al, 2003). Later (>615 Ma) Ediacaran Laurentian paleopoles are controversial (e.g., Halls et al, 2015;McCausland et al, 2011), but they all suggest that Rodinia had already broken up .…”
Section: East and Southeast Laurentia -Grenville Orogenmentioning
confidence: 92%
See 1 more Smart Citation
“…The pre-1.45 Ga paleomagnetic record is fragmentary, but is reasonable for the period 1.45-1.0 Ga (e.g., Elming et al, 2014;Pisarevsky et al, 2014). There is a >200 Ma gap in reliable Laurentian paleomagnetic data between ~1000 and ~790 Ma, followed by another ~100 Ma gap between ~720 and 615 Ma (e.g., Pisarevsky et al, 2008;Pisarevsky et al, 2003). Later (>615 Ma) Ediacaran Laurentian paleopoles are controversial (e.g., Halls et al, 2015;McCausland et al, 2011), but they all suggest that Rodinia had already broken up .…”
Section: East and Southeast Laurentia -Grenville Orogenmentioning
confidence: 92%
“…For example, the Sveconorwegian Orogen in southern Baltica (present co-ordinates) is generally inferred to have formed through continental collision with Amazonia during Rodinia assembly and be contiguous with the Grenville Orogen (Bingen et al, 2008c;Gower et al, 1990;Park, 1992) but recently formation of the orogen in an accretionary setting on the margin of Rodinia has been proposed (Slagstad et al, 2013a). The assembly of Amazonia and Laurentia has been related to both oblique or orthogonal collision, dependent in part on the relative positions of these cratons before and after collision (e.g., Dalziel, 1997;Evans, 2013;Johansson, 2009;Park, 1992;Pisarevsky et al, 2014;Pisarevsky et al, 2003;Tohver et al, 2004b). Some models have questioned whether Amazonia was the colliding element or even if there was collisional orogenesis (Dalziel et al, 2000;Evans, 2009;Santos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although outside the geographical scope of this paper, both of these belts are relatively well known and a wealth of geochronological information is available (summarized by Hanson 2003), including a well-dated, robust, Rodinian palaeomagnetic pole from the Kalahari Craton itself (Powell et al 2001). On the basis of this result, Powell et al (2001) and Pisarevsky et al (2003) concluded that the Kalahari Craton, along with its counterpart Grunehogna fragment in East Antarctica, may have been situated within Rodinia near the western margin of the Australian Craton until 800-750 Ma (Fig. 4).…”
Section: Were the Congo-tanzania-bangweulu And/or Kalahari Cratons Pamentioning
confidence: 99%
“…Dalziel 1997;Li et al 2003;Loewy et al 2003;Pisarevsky et al 2003), then the A-type magmatism and associated rifting could have been related to supercontinent break-up. The timing of Neoproterozoic rifting events in this part of Rodinia was reviewed by Li et al (2003Li et al ( , 2004) and a comparison of the timing of Neoproterozoic magmatism is shown in Figure 6.…”
Section: Neoproterozoic Magmatism Rifting and Sedimentary Basinsmentioning
confidence: 99%
“…One possibility is an increased flux of light hydrothermal source-derived Si into the oceans associated with Neoproterozoic breakup of Rodinia (e.g. Dalziel, 1997;Pisarevsky et al, 2003;Evans, 2009). However, this does not explain why values begin to decline as early as 1.2 Ga.…”
Section: Toward Understanding the Temporal Variation In The Si Isotopmentioning
confidence: 99%